The First Annual Muslim Peacebuilding, Justice, and Interfaith Dialogue (American Journal of Islam and Society, 2006)
The First Annual Muslim Peacebuilding, Justice, and Interfaith Dialoguewas held on 28-30 April 2006. Sponsored by the Salam Institute for Peaceand Justice (SIPJ) and the Islamic Society of North America (ISNA), it wasmade possible through a Conflict Transformation Grant, in part with theFuller Theological Seminary, and the generous support provided by theMohammed Said Farsi Chair of Islamic Peace at American University.The conference was opened by Mohammed Abu-Nimer (SIPJ) andLouay Safi (ISNA). Abu-Nimer explained that this event was being held to“systematically think about the Islamic perspectives of peacebuilding, conflictresolution, and interfaith dialogue, and to attempt to bring it into theAmerican public context.” Safi mentioned that “it is crucial that we learnhow to prevent and resolve these inevitable conflicts.” After these openingremarks, the panel sessions began.Panel 1, “Peace through Development: Experiences from Muslim Communitiesand the Muslim World,” discussed the effect of development practicesin Muslim communities on the peace and sustainability of both thesecommunities themselves and their outside interactions. Kathleen Meilahnspoke about the United States’ inability to create a sustainable peace in Iraqdue to its lack of cultural and religious understanding. She was followed byAyse Kadayifici-Orellana, who presented the SIPJ’s study on MuslimPeacebuilders in Africa and the Balkans. Her major findings included theuse of and the need to expand the concept of tawhid (that all of creationemanates from God) and therefore must understand unity through plurality.Putut Widjanarko’s presentation focused on the Muslim community’s contributionto reducing ethnic differences within Islam.Panel 2, “Intra-Muslim Dialogue,” focused on the need for intra-faithdialogue among Muslims. The presenters pinpointed the Sunni-Shi`ah spilt,differences between converted Muslims and born Muslims, and ideological ...